EFFECT OF CHARACTER EDUCATION ON THE OUTCOME OF INDONESIAN LANGUAGE LEARNING CLASS XI SMAN 1 TAKALAR - Hamzah Hamzah; Sitti Rabiah; Nurfathana Mazhud (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine the effect of character education on the learning outcomes of Indonesian class XI students of SMA Negeri 1 Takalar. This research is a classroom action research conducted in two cycles. Each cycle has four stages, namely, the planning stage, the implementation stage, the observation and evaluation stage, and the reflection stage. The results of this study indicate that the process of implementing the first cycle of learning is not optimal, namely 60.34%, it is different in the second cycle which changes more effectively, which is 84.17%. It is proven that in cycle II, students are more enthusiastic and motivated in participating in the learning process. It shows that the influence of the application of character education on Indonesian language learning outcomes in class XI students of SMA Negeri 1 Takalar can successfully change students' character optimally. Based on the results of the study, it can be concluded that the influence of the application of character education on the learning outcomes of Indonesian class XI IPA 4 students at SMA Negeri 1 Takalar can successfully change the student's character optimally.